2017
DOI: 10.7717/peerj.3289
|View full text |Cite
|
Sign up to set email alerts
|

Network science meets respiratory medicine for OSAS phenotyping and severity prediction

Abstract: Obstructive sleep apnea syndrome (OSAS) is a common clinical condition. The way that OSAS risk factors associate and converge is not a random process. As such, defining OSAS phenotypes fosters personalized patient management and population screening. In this paper, we present a network-based observational, retrospective study on a cohort of 1,371 consecutive OSAS patients and 611 non-OSAS control patients in order to explore the risk factor associations and their correlation with OSAS comorbidities. To this en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 56 publications
(82 reference statements)
1
29
0
Order By: Relevance
“…Evidence from a network-based cluster analysis suggests that populations with OSA are much more diverse than traditionally conceived because there are clusters of nonobese, thin-necked, normotensive individuals with OSA. 60 Certain phenotypes of OSA, such as those with high arousal threshold 44 or high loop gain, 61 are underrecognized and may not be apparent immediately from the results of conventional PSG. Those with the phenotype with high arousal threshold have a low propensity to wake with obstructive events, which may predispose them to a greater magnitude of hypoxemia and hypercarbia within a respiratory event vs those in a patient with a similar AHI.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a network-based cluster analysis suggests that populations with OSA are much more diverse than traditionally conceived because there are clusters of nonobese, thin-necked, normotensive individuals with OSA. 60 Certain phenotypes of OSA, such as those with high arousal threshold 44 or high loop gain, 61 are underrecognized and may not be apparent immediately from the results of conventional PSG. Those with the phenotype with high arousal threshold have a low propensity to wake with obstructive events, which may predispose them to a greater magnitude of hypoxemia and hypercarbia within a respiratory event vs those in a patient with a similar AHI.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between OSA and metabolic disorders is intensively analyzed nowadays and OSA is described as an independent risk factor for onset and progression of T2DM and IR, the mechanisms underlying these processes remain not fully elucidated. Better understanding of this link may lead to a more efficient diagnostic process, as well as facilitate personalized treatment strategy (Mihaicuta et al, 2017;Carberry et al, 2018). Possibly underlying mechanisms include hypoxia, sleep fragmentation, inflammation, and oxidative stress, hormonal changes or increased sympathetic tone (Mesarwi et al, 2015;Farr and Mantzoros, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Severe nocturnal hypoxaemia was found in relatively young, severely obese patients who accounted for about half of the total sample, whereas elderly patients with mild nocturnal hypoxaemia and few symptoms accounted for ∼8% of the total sample. Finally, MIHAICUTA et al [92] published a detailed single-centre study including >1300 OSA patients and >600 controls, and identified eight clusters. This complex study assessed not only single comorbidities, but also their overlap in OSA patients, and identified two clusters of female OSA.…”
Section: Clinical Phenotypes Of Osamentioning
confidence: 99%